Community Empowerment for Environmental Health in the Natural Tourism of Umbul Udal-Udalan: International Community Services - Setiawan, Ari; Luhgiatno, Luhgiatno; Marsum, Marsum; Fatimah, Fatimah; Harun, Makmur; Josiah, Trisnowati; Uslan, Uslan; Tapotubun, Alfonsina Marthina (IMPACTS: International Journal of Empowerment and Community Services, 2025)
Purpose Provide information related to the importance of developing a nature-based tourism village, Providing understanding related to maintaining the environmental conditions of natural tourism umbul udal-udalan, Provide various strategies to maintain the environment so that it is maintained, Provide basic knowledge of waste management around the umbul udal-udalan tourist area. Methods - Implementation of community service activities to this community is directed to eliminate indicators of the existence of environmental problems in the partner area, namely environmental management in the umbul udal-udalan tourist village area inadequate and not in accordance with the the character of the mountainous environment. Transfer knowledge about strategies for protection and waste management in the umbul udal-udalan tourism area, waste management by using best practice, providing assistance and counseling in utilizing waste. Result and discussions - The service was successfully carried out well, this was evidenced by the enthusiasm of the participants who participated in a series of activities during the service. Participants gave a positive response as evidenced in the activities during the service, besides that the participants expressed their satisfaction in participating in this activity because of the increased knowledge related to community empowerment and environmental management of the umbul udal-udalan tourist area. Conclusion - The achievements of the activities or results obtained from this service are: The service was successfully carried out well, this is evidenced by the enthusiasm of the participants who participated in the activities during the service by paying attention to each material provided. Participants gave a very good response as evidenced by the many questions and discussions during the service, besides that the participants expressed their satisfaction in participating in this activity through the responses given when the service was over.